Hubungan Status Sosial Ekonomi Dengan Perilaku Hidup Bersih Dan Sehat Di Masyarakat Perkotaan - Kubangun, Nur Aida; Mulat, Trimaya Cahya (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Clean and Healthy Living Behavior (PHBS) is an important indicator in improving public health. Socioeconomic factors are believed to influence health behavior patterns, particularly in heterogeneous urban communities. This study aims to determine the relationship between socioeconomic status and PHBS in urban communities. The research method used was an analytical survey with a cross-sectional approach. A sample of 120 households was selected using purposive sampling in urban areas. The research instrument was a questionnaire measuring socioeconomic status (education, occupation, and income) and PHBS. Data analysis used the Chi-Square test. The results showed a significant relationship between socioeconomic status and PHBS (p < 0.05). It was concluded that the better a person's socioeconomic status, the more likely they are to implement PHBS in their daily lives. These findings are expected to form the basis for community-based health intervention programs in urban areas.